The effect of eccentric phase duration on maximal strength, muscle hypertrophy and countermovement jump height: A systematic review and meta-analysis - Amdi, C. H.; King, A. (Journal of Sports Sciences, 2025)
The duration of the eccentric phase may affect resistance training (RT) adaptations, with narrative reviews yielding equivocal conclusions. Thus, five databases were searched following Cochrane and PRISMA-guidelines, to compare RT outcomes following shorter (SEG) and longer (LEG) eccentric phase durations. A prospectively registered (https://osf.io/s6uqn/) random-effects multi-level meta-analysis with robust variance estimation was performed for strength, hypertrophy and countermovement jump height (CMJ), with results interpreted relative to a region of practical equivalence. Evidence quality was assessed using the Cochrane RoB 2 and GRADE criteria. Nine studies involving 166 participants (46% trained, 77% male) were included. SEG enhanced CMJ by a practically worthwhile degree with moderate certainty (Hedge`s g = -0.73 [90% CI = -1.34, -0.12; 90% PI = -1.34, -0.12]), while uncertain estimates were observed for maximal strength (g = 0.25 [90% CI = -0.17, 0.67; 90% PI = -0.86, 1.36]) and muscle hypertrophy (g = 0.05 [90% CI = -0.22, 0.33; 90% PI = -0.54, 0.64]). LEG led to practically equivalent or enhanced strength gains, compared to SEG, in trained participants (g = 0.33 [90% CI = 0.07, 0.60; 90% PI = 0.07, 0.60]) and volume-load matched trials (g = 0.25 [90% CI = 0.04, 0.45; 90% PI = 0.04, 0.45]) with moderate certainty in subgroup analyses. Therefore, SEG enhance CMJ, while LEG may cause similar or higher strength increases in trained participants and volume-load matched conditions. However, more research is needed.